2008
DOI: 10.1124/dmd.108.023200
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Diclofenac by Breast Cancer Resistance Protein (ABCG2) and Stimulation of Multidrug Resistance Protein 2 (ABCC2)-Mediated Drug Transport by Diclofenac and Benzbromarone

Abstract: ABSTRACT:Diclofenac is an important analgesic and anti-inflammatory drug, widely used for treatment of postoperative pain, rheumatoid arthritis, and chronic pain associated with cancer. Consequently, diclofenac is often used in combination regimens and undesirable drug-drug interactions may occur. Because many drug-drug interactions may occur at the level of drug transporting proteins, we studied interactions of diclofenac with apical ATP-binding cassette (ABC) multidrug efflux transporters. Using Madin-Darby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 30 publications
(61 reference statements)
0
39
1
Order By: Relevance
“…Similar to rats, canalicular DCF-AG excretion would likely have been mediated by Mrp2 given the 88% protein sequence homology between mouse and rat Mrp2 (Altschul et al, 2005). Another canalicular transporter, breast cancer resistance protein (Bcrp/Abcg2), has been also demonstrated to transport DCF (Lagas et al, 2009). However, exploratory studies in our laboratory with Bcrp-KO mice resulted in equivalent DCF-AG biliary excretion compared with WT (data not shown).…”
Section: Discussionmentioning
confidence: 43%
“…Similar to rats, canalicular DCF-AG excretion would likely have been mediated by Mrp2 given the 88% protein sequence homology between mouse and rat Mrp2 (Altschul et al, 2005). Another canalicular transporter, breast cancer resistance protein (Bcrp/Abcg2), has been also demonstrated to transport DCF (Lagas et al, 2009). However, exploratory studies in our laboratory with Bcrp-KO mice resulted in equivalent DCF-AG biliary excretion compared with WT (data not shown).…”
Section: Discussionmentioning
confidence: 43%
“…This may be due either to direct transport of diclofenac by Pdr5p or to secondary effects of Pdr5p deletion or overexpression (40). Interestingly, a murine homolog of Pdr5p, BCRP1 (ABCG2), can efficiently transport diclofenac in vitro (24). Previously, Mima et al (34) found that overexpression of the polyamine transporter encoded by TPO1 decreases sensitivity to diclofenac in yeast.…”
Section: Vol 77 2011mentioning
confidence: 99%
“…Several drugs have been identified as substrates and/or inhibitors of BCRP by means of in vitro studies. Substrates include antivirals [e.g., acyclovir (Jonker et al, 2005)], statins [e.g., pravastatin (Matsushima et al, 2005) and rosuvastatin (Huang et al, 2006)], anticancer drugs [e.g., topotecan (Maliepaard et al, 1999)], antibiotics [e.g., ciprofloxacin and ofloxacin (Ando et al, 2007)], as well as diclofenac (Lagas et al, 2009), sulfasalazine (van der Heijden et al, 2004, and cimetidine (Jonker et al, 2005). Furthermore, endogenous substances and metabolites such as vitamin K 3 (Shukla et al, 2007), estrone-3-sulfate, dehydroepiandrosterone sulfate (Suzuki et al, 2003), and uric acid (Woodward et al, 2009) have been shown to be transported by BCRP.…”
Section: The Mdr/tap Family (Abc Family Abcb)mentioning
confidence: 99%